Alactic base excess (ABE): a novel internal milieu parameter—its concept and clinical importance (2024)
Inspired by the Stewart-Figge acid–base approach, Gattinoni et al. recently introduced a new internal milieu parameter known as alactic base excess (ABE). The authors defined ABE as the sum of lactate and standard base excess. In the context of sepsis, ABE has been proposed as a valuable marker to discern between metabolic acidosis resulting from the accumulation of lactate and the retention of fixed acids, which can occur in cases of renal failure. Multiple studies have demonstrated that a negative ABE value (<−3 mmol/L) represents an early marker of renal dysfunction, and significantly correlates with higher mortality rates in septic patients. In conclusion, ABE is a simple and useful parameter that can be used to better interpret a patient’s acid–base status, assess renal function, and general prognosis in sepsis. By incorporating ABE into clinical practice, healthcare professionals can enhance their understanding of the complex acid–base imbalances in their patients and tailor more individualized, effective treatment plans.